Vers une reproblématisation des assises d’une théorie du curriculum - Jonnaert, Philippe (Linguarum Arena, 2015)
This article is in the current turmoil of education systems engaged in complex processes of reform and adapting their curriculum. Relieving the outset of the curriculum when it undergoes reduction is assimilated like an educational program, the article establishes a hierarchical inclusion relationship between the two concepts: a curriculum includes educational programs and not the reverse. Positioned downstream of educational policies and upstream of teaching practice, curriculum acts as a transmitter of educational policies towards pedagogical action. The work of educational policies transmitter is specified through a curricular transposition process. The different steps of the process are embodied in the reality of an education system by the various curriculum businesses Finally, a conceptual framework organizes the concept of curriculum around three functional managers.